+0  
 
+1
61
1
avatar

Hallo,

 

wie stelle ich hier auf h2 um?

 

P2 = P1+P*G*(h1+h2)

 

Danke für die Lösungen!

 27.06.2019
 #1
avatar+22484 
+2

wie stelle ich hier auf h2 um?

P2 = P1+P*G*(h1+h2)

 

\(\begin{array}{|rcll|} \hline P_1+P\cdot G\cdot (h_1+h_2) &=& P_2 \quad &| \quad - P_1 \\ P\cdot G\cdot (h_1+h_2) &=& P_2 -P_1 \quad &| \quad :P\cdot G \\ h_1+h_2 &=& \dfrac{P_2 -P_1}{P\cdot G} \quad &| \quad - h_1 \\ \mathbf{ h_2 } &=& \mathbf{ \dfrac{P_2 -P_1}{P\cdot G} - h_1 } \\ \hline \end{array}\)

 

laugh

 28.06.2019

6 Benutzer online

avatar
avatar